2014
DOI: 10.1111/psyg.12055
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of immune globulin intravenous (human), 10% solution in Japanese subjects with mild to moderate Alzheimer's disease

Abstract: IGIV is generally safe and well tolerated with multiple intravenous infusions at doses of 0.2 g/kg and 0.4 g/kg in Japanese patients with mild to moderate Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…We did not evaluate risk of bias for one study because it did not assess the primary outcome. 35 Overall, two studies were at low risk of bias. 36,37 One study was deemed at high risk of bias due to early termination, 40 while the remaining one was deemed as having some concerns due to missing outcome data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We did not evaluate risk of bias for one study because it did not assess the primary outcome. 35 Overall, two studies were at low risk of bias. 36,37 One study was deemed at high risk of bias due to early termination, 40 while the remaining one was deemed as having some concerns due to missing outcome data.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve records describing six trials (788 patients) were included in the systematic review. [35][36][37][38][39][40] Results for one trial were available solely from conference abstracts and were not reported in a way that could be used in a meta-analysis. 38 Data were requested from the corresponding author, 41 but were not made available; hence, this study was reviewed but could not be incorporated in the meta-analysis.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another approach aimed at treating symptoms in patients with mild-to-moderate AD include the use of immune globulin intravenous (IGIV 10 %), a biologic agent containing human immunoglobulin IgG antibodies with anti-inflammatory and immunomodulating properties. IGIV binds to oligomeric and amyloid-β fibrils to reverse neurotoxic events in clinical and preclinical settings [ 43 ].…”
Section: Reviewmentioning
confidence: 99%